1986
DOI: 10.1136/oem.43.2.75
|View full text |Cite
|
Sign up to set email alerts
|

Non-Hodgkin's lymphoma and exposure to phenoxyherbicides, chlorophenols, fencing work, and meat works employment: a case-control study.

Abstract: A previous case-control study which used the occupational information available on the New Zealand Cancer Registry found that agricultural workers were at increased risk of developing non-Hodgkin's lymphoma. The findings are now presented for the second phase of the study which entailed interviewing 83 cases of non-Hodgkin's lymphoma registered under code 202 of the International Classification of Diseases together with 168 controls with other types of cancer and 228 general population controls. The findings f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(49 citation statements)
references
References 18 publications
2
46
0
Order By: Relevance
“…The risk increase ratios vary between 0.9 and 4.7 (Hardell et al, 1981;Pearce et al, 1986, Woods et al, 1987Olsson et al, 1988;Kogevinas et al, 1995;Pahwa et al, 2012). The relationship between the use of pesticides and development of NHL has also been investigated in two cohort studies, which identified a borderline increase in risk (Kogevinas et al, 1997;Bertazzi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…The risk increase ratios vary between 0.9 and 4.7 (Hardell et al, 1981;Pearce et al, 1986, Woods et al, 1987Olsson et al, 1988;Kogevinas et al, 1995;Pahwa et al, 2012). The relationship between the use of pesticides and development of NHL has also been investigated in two cohort studies, which identified a borderline increase in risk (Kogevinas et al, 1997;Bertazzi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…They involve agricultural occupations [7][8][9][10][11][12] and contact with cattle. [13][14][15][16][17][18] Several authors also report an elevated risk for these neoplasms in butchers, abattoir workers and meat cutters. 16,19,20 Additional incriminated factors were occupational exposure to pesticides, industrial paints and solvents, forestry work, the leather industry and hair dyes.…”
Section: Epidemiologic Datamentioning
confidence: 99%
“…Many epidemiologic studies have been conducted and are currently underway to evaluate the chronic effects of these pesticides in occupational groups, such as manufacturers, professional turf applicators, farmers, forestry and railroad workers, Vietnam veterans and others ( Axelson et al, 1980;Ott et al, 1980;Riihimaki et al, 1982;Coggon et al, 1986;Coggon et al, 1991;Hoar et al, 1986;Pearce et al, 1986;Hoar Zahm, 1987;Lynge, 1987;Lynge, 1993;Vineis et al, 1987;Bond et al, 1988;Eriksson et al, 1990;Wigle et al, 1990;Green, 1991;Lerda and Rizzi, 1991;Saracci et al, 1991;Swaen et al, 1992;Bloemen et al, 1993;Bueno de Mesquita et al, 1993;Kogevinas et al, 1993;Kogevinas et al, 1997;Alavanja et al, 1996;Zahm, 1997;Zahm et al, 1990). Although the current weight of epidemiological evidence suggests an association between the use of 2,4 -D and some cancers, a cause -effect relationship has not been established.…”
Section: Introductionmentioning
confidence: 99%